The effect of shortening and lengthening round periods exercises in the development of special endurance and some pulse indicators in elite boxers - dr. Abduljaleel Jabbar Nasir (الرياضة المعاصرة)
The researcher noticed some weakness in the special endurance of boxers, at the end of rounds, especially at the end of the last round, the researcher suggested special exercises using the method of shortening or lengthening the training rounds time, to develop special endurance and some pulse indicators, the researcher chose 14 boxers that were divided equally into two groups, control and experimental, the researcher used the times: (30 sec.), (60 sec.) and (90 sec.), with rest times between (15 sec. and  60 sec) and (4 minutes), (5 minutes), (6 Minutes) with rest times between (30 sec. to 90 sec.), The repetitions for each round were downwards according to the time period of the round, the researcher concluded that training using shortening and lengthening exercises time has a positive effect in developing the endurance level and some pulse indicators for boxers from the research sample.